Nursing care of a hemodialysis patient after parathyroidectomy (1例血液透析患者甲状旁腺切除术后的护理体会) - ZHANG Yunfeng (张云凤); WEI Yu (魏宇); SONG Yali (宋雅丽); JIA Hengxia (贾恒霞); MA Ning (马宁); ZHAO Shuya (赵淑娅); ZHANG Zijun (张子君); LI Jie (李杰); ZHOU Yingping (周颖萍) (中西医结合护理)
This paper summarized the nursing management for a hemodialysis patient after parathyroidectomy for secondary hyperparathyroidism. The nursing measures included timely correction of hypocalcemia, dietary nursing, psychology nursing and health education about medication. Comprehensive nursing intervention is potentially effective to improve the comfort level, treatment compliance and quality of life in the hemodialysis patient after parathyroidectomy. (本文总结1例血液透析合并继发性甲状旁腺功能亢进症患者甲状旁腺切除术后的综合护理经验, 护理要点包括及时纠正低钙血症、饮食护理、心理护理和相关知识宣讲以及合理用药, 通过综合护理能有效改善患者不适症状, 提高治疗依从性和生存质量。)